Analisis Usaha dan Strategi Pemasaran Rabok Ikan Layang (Decapterus spp) Bawang Dayak di Kota Samarinda (Studi Kasus UMKM Aqueena) - Ulfa Aprilyani; Muhammad Syafril; Wahyu Fahrizal (Faculty of Science and Technology University Ibrahimy, 2026)
The purpose of this study is to analyze the feasibility of the production business of layang fish (Decapterus spp) with Dayak onion seasoning by using indicators such as Revenue Cost Ratio (RCR), Break Even Point (BEP), Payback Period (PP), Return on Investment (ROI), and to describe the marketing strategies implemented by the layang fish processing business at UMKM Aqueena. This research is a case study. Sampling was conducted using purposive sampling. The results show that the layang fish processing business with Dayak onion seasoning at UMKM Aqueena is financially feasible and profitable, indicated by a net monthly profit of IDR 20,378,858. The Revenue Cost Ratio (RCR) value is 2.83. The Break Even Point (BEP) is reached at 247 packages per month, with a BEP price of IDR 15,887 per package and BEP sales of IDR 72,609 per month. The BEP condition is below the actual business level. The payback period for the investment is only 1.01 months, and Return on Investment (ROI) reaches 99%. There are five marketing strategies applied by the business owner: product strategies and services (product development, product diversification, product labeling, packaging, and labeling, as well as product guarantees and services); organizational structure and service strategies (division of labor with clear responsibilities); sales increase strategies (advertising through banners and brochures), including quality advertising, factual advertising, institutional advertising, and sales promotions via WhatsApp, Facebook, and Instagram; pricing strategies (setting actual prices); and physical arrangement and product display strategies (placing products in open display cases). These strategies have strengthened the business's sustainability and competitiveness for the future. Keywords: Feasibility analysis, marketing strategy, flying fish rabok